An Evaluation of ICT Integration in Science Learning in Primary Schools in Saudi Arabia - Alharthi, Alaa Abdulaziz S (Curtin University, 2018)
Technology plays an important role in education, and Saudi Arabia has dedicated a huge budget to develop technology for education. The aim of this mixed-methods study is to evaluate ICT integration in science education in upper primary schools by investigating both students’ and teachers’ perceptions of ICT use. Participants perceived the ICT integration positively but faced several challenges including time and technical issues. Many participants suggested providing devices to improve Saudi science education.